Estrategia del rendimiento de la calidad como factor competitivo en educación a distancia y educación superior en educación universitaria (Papeles, 2010)
This project tackled the problem of the qualification of the learning, establishing a comparison between the results of this one and the achievements generated in the Actual Education, obligated reference of this comparison. We can’t be ignorant of the close relation of the education with the social, economic, cultural and politic processes, not only at the beginning of a program of this kind, but permanently. The higher education has as objective the achievement of a suitable professional, independently that his precedence is the Actual or the Distance University. The results of both modalities should be alike for a similar performance in similar social-economic, cultural and political circumstances.